2014
DOI: 10.1115/1.4027633
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Geometric Shapes on the Hydrodynamic Lubrication of a Partially Textured Slider With Micro-Grooves

Abstract: The effect of partial surface texturing in the form of parabolic grooves, rectangular grooves, and triangular grooves on the hydrodynamic pressure is investigated in the present work. The dimensionless hydrodynamic pressure generated by the partial surface texturing is obtained by the multigrid method. The effect of the texturing parameters on the dimensionless average pressure is analyzed for a given set of operating parameters. The results indicate that the geometric shape, area density, groove depth, and or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 33 publications
3
28
3
Order By: Relevance
“…That is, both the dimensionless mesh-sizes of the finest mesh, DX and DY , are equal to 0.125. Therefore, the number of nodes of the finest mesh n 3 m can be calculated by the following equations (20) and (21)…”
Section: Methodsmentioning
confidence: 99%
“…That is, both the dimensionless mesh-sizes of the finest mesh, DX and DY , are equal to 0.125. Therefore, the number of nodes of the finest mesh n 3 m can be calculated by the following equations (20) and (21)…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, the possibility of enhancing the bearing performances by opening micro‐grooves in the bearing surfaces has attracted attention of many researchers, and they have performed many theoretical and experimental investigations. Most theoretical and experimental investigations explore micro‐grooved bearings using an incompressible lubricant . Fu et al .…”
Section: Introductionmentioning
confidence: 99%
“…Most theoretical and experimental investigations explore micro-grooved bearings using an incompressible lubricant. [1][2][3][4][5][6][7] Fu et al 1 investigated the load-carrying capacity of micro-grooved hydrodynamic parallel slider bearings by the multi-grid method. Their work showed that the load-carrying capacity increases with the increase of the groove width, but the load-carrying capacity increment decreases with the increase of the groove width.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface texturing has a remarkable influence on the tribological properties of friction pair surfaces [1][2][3]. It can be produced by Laser processing technology [4], reactive ion etching technology [5], photochemical machining technology [6], machining technology, and so on.…”
Section: Introductionmentioning
confidence: 99%